Can Difficulties in Language Acquisition and Specific Learning Disabilities Be Separated Among English Learners?. (April 2020) - Swanson, H. Lee; Kong, Jennifer; Petcu, Stefania D.; Asencio Pimentel, Monica Fiorella
This study investigated the prevalence of latent classes at risk for reading or math disabilities in elementary-age children whose first language is Spanish. To this end, children ( N = 394) in Grades 1, 2, and 3 were administered a battery of vocabulary, reading, math, and cognitive measures in both Spanish and English. Three important findings occurred. First, five latent classes emerged (average achievers, poor achievers, reading disabled, English language learners, Spanish-dominant achievers) that varied in language and achievement scores. Second, probability estimates indicated that 10% of the total sample was at risk for learning disabilities (below cutoff score), and approximately 40% of the sample reflected a language acquisition group not at risk for academic difficulties. Finally, the best model for correctly predicting the odds of latent classes differing from average achievers included English measures of short-term memory, naming speed, and the executive component of working memory. The results support the notion that statistically distinct latent classes emerge under the umbrella of children identified as English learners and that children at risk for specific learning disabilities can be separated among a heterogeneous sample of children who are acquiring English as a second language.